Sustainable Development Management and Building a New Civilization - Piontek, Franciszek (Problemy Ekorozwoju, 2021)
The objective of the paper is to: analyze and assess assumptions which determine the functioning of the category of management; identify the criteria and assumptions of integrated sustainable development management. The hypothesis: Integrated sustainable development management requires: Necessary conditions: the verification of the institutional solutions which function between the category of sustainable development and development concepts based on sustainability and unsustainability and between these concepts and management. Sufficient conditions: the decision-making will in accepting this verification, its assumptions and criteria, including the rules of universal procedures. Final conclusion: Limiting the paradigm of consent, based on the paradigm of deregulation and institutional solutions, which limit creative decisions.